2013
DOI: 10.1097/iae.0b013e318285cbef
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Detachment and Proliferative Vitreoretinopathy

Abstract: Endothelin 1 has shown a close relationship with IOP and CRA blood flow changes associated to retinal detachment as well as with proliferative vitreoretinopathy complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“… 12 Previous reports showed a relationship between RRD and endothelin-1 (ET-1), which is a powerful vasoconstrictor peptide, and increased levels of ET-1 in the plasma and subretinal fluid in patients with RRD. 18 Our previous study reported that the macular vascular flow recovered after surgery for RRD, and it was suggested that the macular flow in eyes with macula-on RRD may undergo a reversible change. 15 Therefore, although SLDF can detect temporal changes in the velocity as a result of vasoconstriction, OCTA can detect the vascular structural changes that may be detected as capillary dropout.…”
Section: Discussionmentioning
confidence: 93%
“… 12 Previous reports showed a relationship between RRD and endothelin-1 (ET-1), which is a powerful vasoconstrictor peptide, and increased levels of ET-1 in the plasma and subretinal fluid in patients with RRD. 18 Our previous study reported that the macular vascular flow recovered after surgery for RRD, and it was suggested that the macular flow in eyes with macula-on RRD may undergo a reversible change. 15 Therefore, although SLDF can detect temporal changes in the velocity as a result of vasoconstriction, OCTA can detect the vascular structural changes that may be detected as capillary dropout.…”
Section: Discussionmentioning
confidence: 93%
“…11 The release of the vasoconstrictive endothelin-1 by endothelial glial cells could be a further significant factor. Roldan-Pallares et al 29 identified this peptide in subretinal fluid accumulations. This release fits to the observation that perfusion of the retinal microvasculature is reduced.…”
Section: Discussionmentioning
confidence: 97%
“…11 The release of the vasoconstrictive endothelin-1 by endothelial glial cells could be a further significant factor. Roldan-Pallares et al 29 Fig. 4.…”
Section: Discussionmentioning
confidence: 98%